Hospital financial performance: Effectiveness, efficiency and economic approach - Putra, Afuan Fajrian; Maharani, Dinda Wahyu; Shafir, Annisa Fidanta (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to determine the financial performance of public sector organizations by using the effectiveness, efficiency and economic ratios of the financial reports of the Batang Regional General Hospital in 2019-2021. The type of data used is secondary data in the form of Financial Financial Reports, namely LRA (Budget Realization Report. The results of the Batang Regional Hospital analysis show that the effectiveness ratio in 2019 was 81.02% and was categorized as quite effective, in 2020 it experienced an increase of 93.74%, categorized as effective and in 2021 there was an increase of 118.49%, categorized as very effective. The efficiency ratio in 2019 was 112.21% and categorized as very inefficient, in 2020 it decreased by 91.25%, it was categorized as inefficient and in 2021 it decreased again by 81.10% in the quite efficient category. The economic ratio in 2019 was 91.11% and categorized as economical, in 2020 it decreased by 83.09%, categorized as quite economical, and in 2021 it experienced an increase of 96.10% and was categorized as economical.